Digitally Endangered Species: The BitList - Middleton, Sarah; Kilbride, William (KULA)

(untitled) (University of Victoria Libraries, 2018)
The Digital Preservation Coalition (DPC) is a not-for-profit professional membership organisation that enables its members to deliver resilient long-term access to digital content and services, helping them to derive enduring value from digital assets and raising awareness of the strategic, cultural and technological challenges they face. The Coalition achieve its aims through advocacy, community engagement, workforce development, capacity-building, good practice and good governance.On 30 November 2017, as part of its ongoing advocacy work and the first International Digital Preservation Day, the DPC published the first ‘BitList.’ This list presented the results of a crowd-sourcing exercise that sought to discover which digital materials the digital preservation community thinks are most at risk, as well as which materials are relatively safe thanks to digital preservation.